Males de amor. Una comparación entre el episodio de Marcela y Grisóstomo del Quijote y el episodio de Francesca y Paolo de la Comedia - Gatti Murriel, Carlos (2011)
This article compares characters and situations regarding two relevant scenes of, respectively, Cervantes’ Quijote and Dante’s Divine Comedy: Don Quijote, Sancho Panza, Dante, Vergil, Grisóstomo, Paolo and, most notably, Marcela and Francesca. Marcela and Francesca’s stories are interpreted in the light of several points of view, the most interesting of them being that of the «Love Palace» described in Andrea Cappellano’s De Amore. Marcela’s frigidity and Francesca’s lewdness are interpreted as illnesses as they take different places in the «Love Palace».